Modern methods in enterprise development management - Drepin, Ivan (National Technical University "Kharkiv Polytechnic Institute", 2024)
The research proposes to use digital marketing in enterprise development management. Analyzed the advantage and opportunity of using digital tools to achieve business goals. Particular attention is paid to the development of a management model based on digital marketing, as well as methods for assessing the effectiveness of its application.
Keywords: enterprise management; digital marketing; management models; competitiveness; efficiency